Doctor-patient interactions during medical consultations about obesity - Webb, Helena (2009)
The current “obesity epidemic” is a global concern for governments and healthcare organisations. Obesity is seen as a medical problem of excess body weight which can be resolved through interventions to encourage weight loss, most particularly diet and exercise regimes. Much existing sociological work focuses on moral understandings of obesity as a perceived symbol of individual greed and laziness in a culture that prioritises self-control and effort. This neglects the ways in which the condition is actively discussed and managed in relevant settings such as medical encounters. This thesis addresses this research gap by analysing talk during obesity-related medical consultations. Talk is central to all medical encounters and has particular resonance in treatments for obesity where most interventions are carried out by the patient away from the medical gaze. Patients must report on their treatment behaviours in ways that enable practitioners to evaluate them and offer further relevant advice. Talk is not only a means through which treatment is delivered but a form of treatment itself.